Metallographic Analysis Of Coil Springs Against Temperature Variations Using ASTM E-122 and ASTM E-562 - Wisma Soedarmadji; Muhammad Ilham Abdillah (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2021)
All agricultural tools require key components in the manufacturing process, one of which is metal. The metal commonly used in the manufacture of agricultural machinery is a type of steel with a medium carbon content. This type of metal is found in many vehicle parts, so parts with moderate carbon content are spring parts. Therefore, this study was conducted to determine the effect of temperature variations on the manufacture of agricultural equipment products made from coil springs on their mechanical properties. In this study, an analysis of the coil spring steel was carried out. The research methods used included sample pieces, heat treatment with temperature changes of 815 OC, 830 OC and 850 OC, quenching with SAE 20-50 W oil cooling media, hardness test and metallographic test. From the results of the study, the highest percentage of martensite microstructure was at 850 OC temperature specimens with a value of 64% and the lowest percentage was at 830 OC temperature specimens with a value of 42%. The high percentage of bainite microstructure is at 830 OC temperature specimen with a value of 58% and the lowest percentage is at 850 OC temperature specimen with a value of 36%. Meanwhile, the highest percentage of ferrite microstructure is at 815 OC temperature specimens and the lowest percentage is in non heat treated specimens with a value of 40%. By comparison on non-heat treated specimens which have a value of 40% ferrite and 60% pearlite. The microstructure with the largest grain shape is found in the specimen at 850 OC temperature with grain number 4 and the micro structure with the smallest grain shape is found in the specimen at 815 OC having grain number 6 with a comparison of non-heat treated specimens having grain number 7. Obtained an average value – The highest average hardness with oil cooling media on coil spring steel has a hardness value of 76.75 HRC at a temperature of 850°C. While the lowest average hardness value with oil cooling media on coil spring steel has a hardness value of 75.4 HRC, namely at a temperature of 815 °C, with a hardness ratio of 71.3 HRC in the initial conditions without heat treatment.